AKUNTABILITAS KINERJA PEGAWAI PADA KANTOR CAMAT LAMBU KABUPATEN BIMA - Kamaludin Kamaludin; Jasman Jasman; Taufik Irfadat (JURNAL DINAMIKA, 2022)
Employee at the Lambu sub-district office that is the importance of public accountability in order to improve the quality of service by the government bureaucracy as a manifestation of good governance. In the end, it will be able to establish harmony and harmonious relations between the government, the private sector and civil society. The performance of employees at the Lambu sub-district office is a manifestation of the implementation of activities as reflected in the achievement of performance in accordance with the established Vision, Mission, Goals and Targets. Employee performance has very important benefits, besides being the implementation of Strategic Tactical Planning, it is also to show the success of the implementation of the Strategic Plan (Renstra) at the Head of Lambu Office. Performance accountability for employees of the Head of Lambu Office includes the obligation to present and report all actions and activities especially in the field of personnel administration to higher parties/superiors. Employees are one of the vital elements in service. The volume of work and the number of employees are two factors that influence each other in performance accountability. The state of structural officials at the Head of Lambu Office as many as 23 people and staff as many as 22 people